Lactic acid bacteria isolated from the Stingless bee Scaptotrigona mexicana and partial characterization of their probiotic activity - Fernández-Roblero, S.; Vázquez-Ovando, A.; Grajales-Conesa, J.; Rincón-Rabanales, M.; Coronel-Niño, R.; Vázquez-Ovando, A. (Revista Bio Ciencias, 2020)
The objective of this study was to isolate lactic acid bacteria (LAB) from honey produced by the stingless bee Scaptotrigona mexicana from southern of Mexico, and to evaluate their probiotic potential. From fresh and fermented honey, 18 strains were isolated. Of these, 10 had presumptive LAB biochemical characteristics. Their ability to grow at different pH values and different temperatures, susceptibility to antibiotics, and ability to inhibit Salmonella sp. and Escherichia coli were assessed. All the strains tested were resistant or moderately susceptible to penicillin, dicloxacillin, and ampicillin. The strains that showed tolerance to pH 2.5 were the bacteria labeled FIM1 and FIM2, and only strains OP3 and TUX5 were able to grow at 5 °C. Although none of the supernatant growth media of the strains inhibited the development of pathogenic bacteria, other tests should be done to verify the probiotic nature of the strains that exhibited some characteristic of interest.